A Novel Look at Astrocytes: Aquaporins, Ionic Homeostasis, and the Role of the Microenvironment for Regeneration in the CNS. (April 2013) - Mack, Andreas F.; Wolburg, Hartwig
Aquaporin-4 (AQP4) water channels are located at the basolateral membrane domain of many epithelial cells involved in ion transport and secretion. These epithelial cells separate fluid compartments by forming apical tight junctions. In the brain, AQP4 is located on astrocytes in a polarized distribution: At the border to blood vessels or the pial surface, its density is very high. During ontogeny and phylogeny, astroglial cells go through a stage of expressing tight junctions, separating fluid compartments differently than in adult mammals. In adult mammals, this barrier is formed by arachnoid, choroid plexus, and endothelial cells. The ontogenetic and phylogenetic barrier transition from glial to endothelial cells correlates with the regenerative capacity of neuronal structures: Glial cells forming tight junctions, and expressing no or unpolarized AQP4 are found in the fish optic nerve and the olfactory nerve in mammals both known for their regenerative ability. It is hypothesized that highly polarized AQP4 expression and the lack of tight junctions on astrocytes increase ionic homeostasis, thus improving neuronal performance possibly at the expense of restraining neurogenesis and regeneration.